Panmen Favour Kitch Tunes - Unknown (Daily Express)
Pan Trinbago's "Pan Fever 76" saw thousands of people crowded into Skinner Park, San Fernando. The majority of the 27 bands played calypsoes by reigning Road March and Calypso King Lord Kitchener. There are pictures of the mammoth crowd by Onesto Cambridge.
Keywords: Calypso (Music) -- Trinidad and Tobago; Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Calypso musicians -- Trinidad and Tobago